The Art of Regenerative Educatorship (Taylor & Francis, 2025)
A regenerative current is rising all around us. Stories of the need to reconnect, heal and transform are becoming more urgent, challenging a dominant worldview built on competition, economic growth, extractivism, militarisation and personal gain. Our planet's resources are stretched beyond their limits, causing widespread suffering and injustice for both humans and non-humans. Yet, each of us holds the potential to cultivate life-affirming futures. The Art of Regenerative Educatorship offers a hands-on exploration of what it means to answer the call of the regenerative current in the field of education. Grounded in the principles of living systems thinking, this book explores the principles and practices of bringing regeneration into educational spaces. Drawing from a variety of case studies, personal stories and regenerative frameworks, it will inform and inspire your educational artistry. You will find guidance to: Engage in practical exercises to help transform your educational practice; Navigate the interwoven inner, communal, and whole-system paths of regeneration; Develop four core capabilities to regenerate your practice; Lead collaboratively. Rooted in the core virtues of love, presence, and courage, The Art of Regenerative Educatorship is a vital resource for those seeking to breathe new life and purpose into their educational practice, in service to their community, (eco)system and society.